ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA RANTAI PASOKAN PADA BISNIS USAHA MIKRO, KECIL, DAN MENENGAH BIDANG KULINER DI KABUPATEN KENDAL - Muhammad Misbakhul Munir; Bambang Munas Dwiyanto (JURNAL STUDI MANAJEMEN ORGANISASI, 2018)
The development of indonesia’s economy can not be separated from the roles of industries and UMKMs in various regions spread throughout Indonesia. Kendal Regency is one of the potential and developing regions of the industrial sector and UMKM supported by the tourism sector in the area. One of them is the culinary UMKM. However, as in other business fields, even in the culinary sector UMKM have various problems faced such as increasingly fierce competition, difficulty in obtaining access to capital, inadequate marketing, lack of superior resources, lack of access to suppliers, emergence of new competitors , do not have a plan to deal with unexpected things. These problems are included in supply chain management. The purpose of this study is to address the influence of long-term relationship, information sharing, agile, and process integration on the performance of the UMKM supply chain in the culinary field in Kendal Regency.The population in this study culinary UMKM entrepreneurs in Kendal Regency amounted to 925. This study used a sample of 100 respondents through questionnaires, where the data obtained will be analyzed using multiple linear regression analysis using SPSS.The results of this study indicate that the indicators in this study are valid and reliable. The variable that has the greatest influence is agile with the value (0.482), then the process integration variable with the value (0.462), then the information sharing variable with the value (0.342), and the last is the long-term relationship variable with the value (0.218). This result shows that all independent variables in this study have a positive and significant influence on the dependent variable, namely the performance of the UMKM supply chain in the culinary field in Kendal Regency.